Microbial transformation of natural products - Alfarra, Helmi Yousif; Omar, Muhammad Nor (Greener Journals, 2013)
This article revises the current state of microbial transformation use in natural products. It represents the results of the most recent reports. Due to the importance of this transformation, there is still a strong need to intensify the direction of microbial transformation of the natural product compounds, besides exploiting more microorganisms that might be the used biocatalysts in producing the novel materials for pharmaceutical purposes.